Qualidade e atividade antioxidante de frutos de genótipos de umbu cajazeiras (Spondias sp.) oriundos da microrregião de Iguatu, CE. - Silva, Leirson Rodrigues da (2008)
The ‘umbu-cajá’ is a fruit tree species belonging to the Anacardiaceae family which has spontaneous occurrence in the semi-arid region of Northeast, Brazil.This work of research aimed to evaluate the quality of fruits of the tree umbu-cajazeiras (Spondias sp.), from different genotypes, through physical, physical-chemistry and total antioxidant activity. The fruits used in the experiment were harvested from twenty source plants of the tree umbu-caja proceeding from the town Iguatu, CE. The following parameters were evaluated: weight (peel, pulp, seed) diameter, size, yield (peel+pulp), firmness, soluble solids, soluble sugars and reductors, pH, titrable acidity, starch, total and soluble pectin, ascorbic acid, carotenoids, yellow flavonoids, anthocyanins, total extractable polyphenols and antioxidant activity for the method β-carotene/linoleic acid. In a way, it had a variation between the genotypes, for all the evaluated physical characteristcs. The genotypes had presented a average of firmness 2,36N, wheigt of 14,5g and excellent yield pulp (above of 80%) distinguished P17, P5 e P15, factor this of great importance for the industry. With regard to the evaluated attributes of quality, the soluble solids fruits had in above of 10 °Brix, hight content of sugars (6,73%), pH above of 2,5 and above acidity 1% and low for starch (0,17%) and pectin (0,37%). The general vitamin C was 26,55 mg/100 g and phenolics 29,63 mg/100g. The antioxidant activity evaluated by the β-carotene/linoleic acid in three concentrations (5, 15 and 30g/L), had presented a greet variation between the materials and a percentage of innibition of the superiority 50% for all the genotypes in study in the time of 120 minutes.